2014
DOI: 10.1016/j.addbeh.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Family income trajectory during childhood is associated with adolescent cigarette smoking and alcohol use

Abstract: Background Although childhood socioeconomic disadvantage has been linked with adolescent tobacco and alcohol use in cross-sectional research, less is known about the influence of changes in socioeconomic status during childhood. Upward socioeconomic mobility may attenuate the negative influence of earlier socioeconomic disadvantage on health, while downward mobility may counter the health benefits of earlier socioeconomic advantage. This study evaluated the influence of common trajectories of family income dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 39 publications
6
31
0
Order By: Relevance
“…A study conducted in the United States found that childhood SES was adversely related to tobacco and alcohol use in their later life [24]. Tobacco smoking and alcohol drinking have long been recognized as risk factors for both ESCC and EAC [9].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the United States found that childhood SES was adversely related to tobacco and alcohol use in their later life [24]. Tobacco smoking and alcohol drinking have long been recognized as risk factors for both ESCC and EAC [9].…”
Section: Discussionmentioning
confidence: 99%
“…Our prior polygenic risk score analysis in 9863 subjects from the Generation Scotland: Scottish Family Health Study also indicated that the genetic predisposition to alcohol dependence is negatively associated with cognitive function and socioeconomic deprivation (Clarke et al, 2015). It is recognized that alcohol use and abuse are correlated with both lower income and academic achievement (Latvala et al, 2014;Poonawalla et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these predictors, we control for variables that are associated with more frequent/ heavier alcohol use in adolescence: age (wave of data collection), school grades, socioeconomic status (SES; free/reduced price school lunch), and living with both parents (Brown & Rinelli, 2010;Johnston et al, 2016;Poonawalla, Kendzor, Owen, & Caughy, 2014). As norms for alcohol use and susceptibility to social influence change across adolescence (Brechwald & Prinstein, 2011;CDC, 2015;Johnston et al, 2016;Steinberg & Monahan, 2007), we explore whether age moderates each association we examine.…”
Section: The Present Researchmentioning
confidence: 99%